2019
DOI: 10.1186/s12888-019-2080-0
|View full text |Cite
|
Sign up to set email alerts
|

How do adolescents with depression experience improvement in psychodynamic psychotherapy? A qualitative study

Abstract: BackgroundThere is emerging evidence for the effectiveness of psychodynamic psychotherapy for depressive disorders. However, we know less of how this relation-focused therapy mode is experienced and what the patients themselves identify as helpful. Hence, the purpose of this study is to explore adolescents’ experiences of factors promoting improvement in psychodynamic therapy.MethodsEight female patients participating in a Norwegian study on psychodynamic therapy, the First Experimental Study of Transference W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 36 publications
10
45
0
1
Order By: Relevance
“…Our results implied that within the context of family therapy for depressed adolescents, the quality of the therapeutic alliance played an important role in improving the clients' experiences with therapy. This finding is consistent with reports from previous research that, within Chinese and Western culture, trustworthy therapeutic alliances not only constitute the basis of therapy, but also facilitate the process of change for adult and adolescent clients in family and individual therapy (Liu et al, 2013;Yoo et al, 2016;Lovgren et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results implied that within the context of family therapy for depressed adolescents, the quality of the therapeutic alliance played an important role in improving the clients' experiences with therapy. This finding is consistent with reports from previous research that, within Chinese and Western culture, trustworthy therapeutic alliances not only constitute the basis of therapy, but also facilitate the process of change for adult and adolescent clients in family and individual therapy (Liu et al, 2013;Yoo et al, 2016;Lovgren et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Similar to previous research results, our results showed that among the factors affecting the therapeutic alliance, the therapists' personality traits and professional competence, such as their mildness, stability, openness, patience, empathy, attention to clients, meticulousness, skill in collating and analyzing information, and ability to give theoretical explanations, made the clients trust them more (Despland et al, 2009;Sundet, 2011;Anderson and Strupp, 2015;Schottke et al, 2017;Lovgren et al, 2019). This finding may indicate that the form of treatment that depressed adolescents and families need most is humanized attention and acceptance from clinicians.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings align with previous research in highlighting the importance of coping and resilience [17][18][19][20][21]; improved family functioning and relationships [17,24,26,68]; social functioning and connectedness [18,19,67]. In addition, a growing body of qualitative research examining procedural aspects of therapy and facilitators of good outcome is emphasizing the importance of young people feeling heard, listened to, and able to open up without feeling judged [69][70][71][72][73][74]. In this study, experiences of being worthy of another person's attention, of feeling listened to, or of discovering new perspectives on life were described as so transformative by more than a third of adolescents, that they might be considered outcomes in their own right rather than mere facilitators of change.…”
Section: Discussionsupporting
confidence: 88%